SYNTACTIC AND SEMANTIC FEATURES OF ENGLISH DESCRIPTIVE ADJECTIVES IN SOME ENGLISH WORKS WITH REFERENCE TO THEIR VIETNAMESE EQUIVALENTS / Nguyễn Thị Thu Hà; NHDKH Dr Phạm Thị Tuyết Hương - Nguyễn, Thị Thu Hà
This study comparatively analyses the syntactic and semantic features of descriptive adjectives and their Vietnamese equivalents. The analysis is based on the types, different forms and orders of descriptive adjectives in the languages under study. Through chapter 4, some main syntactic and semantic features of descriptive adjectives will be given. For example, in English descriptive adjectives can be a form of compound adjectives, in form and structures of comparison and inversion. In Vietnamese, descriptive adjectives always follow a noun, but sometimes they can stand before noun. This feature is always expressed in poems, proverbs…to emphasize the characteristics of subjects in sentence. It is evident from the findings that descriptive adjectives account largely for tools and mostly used in conversation in both Vietnamese and English, in spoken and written discourses. These aspects are shown in the use of predictive and future temporal descriptive adjectives by both Vietnamese and English speakers. The study recommends further studies on conducting a comparative analysis of English and Vietnamese.